LTE-Advanced: Femtocell Perspective (International Journal of Engineering and Computer Science, 2015)
Femtocells are small cellular telecommunications base stations that can be installed in residential or business environments for better cellular coverage. Information and communications technology ecosystem now represents around 10 per cent of the world's electricity generation and increasing continuously day to day due to increasing the base stations of 4G and LTE-Advanced wireless communications network and it may create a power management problem in near future. According to the Cisco Visual Networking Index: Global Mobile Data Traffic Forecast Update, for 2012-2017, "the overall mobile data traffic is expected to grow to 11.2 Exabyte’s per month by 2017.To minimize the challenge A femtocell is possible solution, It results in a significantly improved signal quality and substantial cost savings also. The aim of this paper is to examine in a top-down approach the femtocells as an important component of the developing LTE-Advanced Technology, with essential projection into the future of the femto-cellular technology and what the future holds for its deployment for operators and also the benefits of Femtocells.